PENATAAN INFRASTRUKTUR KAWASAN PARIWISATA UBUD DALAM MENGHADAPI ADAPTASI KEBIASAAN BARU PASCA PANDEMI COVID-19 - Nyoman Trisna Kurniawan (LPPM Universitas Terbuka, 2022)
The increasing development of tourism activities and the increasing number of tourists in the Ubud Tourism area have resulted in various problems that have an impact on the poor quality ofthe environment in the Ubud Tourism Area. The most crucial problem is congestion caused by various things, and other problems are the condition of infrastructure and utility networks, cleanliness of the area, and limited public green open space. The purpose of this research is to formulate arecommendation concept for structuring the Ubud Tourism Area which can comprehensively be a guide in solving the problem of poor environmental quality, especially in dealing with the adaptation of new habits (new normal) after the Covid-19 pandemic. This study uses a mixedmethod with a descriptive-qualitative analysis method based on policies and relateddocuments. The results obtained from this study are planning for infrastructure arrangement in the Ubud Tourism Area: structuring traffic flow and construction of new roads (ring roads and shortcuts),building parking facilities and the shuttle bus concept, structuring the integrated JalanRaya Ubud, structuring roadside gardens as a public green open space, and the application of the CHSEprotocol concept in the arrangement of the Ubud Tourism Area in adapting new habitsafter theCovid-19 pandemic.